1981
DOI: 10.1007/bf02409429
|View full text |Cite
|
Sign up to set email alerts
|

Relative effectiveness of vitamin D metabolites in increasing bone mineral solubility

Abstract: Weanling rats were given a vitamin D-deficient diet containing 1.4% calcium and 1.0% phosphorus. After 4 weeks these deficient animals were injected for 7 days with selected doses of one of the following vitamin D metabolites: 25(OH)D3, 1,25(OH)2D3, 24,25(OH)2D3, 25,26(OH)2D3 or the ethanol vehicle. A vitamin D-replete group was placed on the same diet but injected with 50 IU of vitamin D3 once a week for the entire 5-week period. By the use of a modified Ussing chamber [1], the measurements of calcium fluxes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1981
1981
2003
2003

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Lastly, the concentration of 25OHD in serum is often reported to be better correlated with absorption of calcium from the intestine and a more important determinant of calcium absorption than is serum 1,25(OH) 2 D [5,6,63]. Thus, from these and other studies [7,51,64,65] it is apparent that 25OHD is capable of substituting for 1,25(OH) 2 D, however usually at higher doses than 1,25(OH) 2 D [4]. Relatively few studies have compared the activities of 25OHD with its parent form.…”
Section: Biological Activitymentioning
confidence: 99%
“…Lastly, the concentration of 25OHD in serum is often reported to be better correlated with absorption of calcium from the intestine and a more important determinant of calcium absorption than is serum 1,25(OH) 2 D [5,6,63]. Thus, from these and other studies [7,51,64,65] it is apparent that 25OHD is capable of substituting for 1,25(OH) 2 D, however usually at higher doses than 1,25(OH) 2 D [4]. Relatively few studies have compared the activities of 25OHD with its parent form.…”
Section: Biological Activitymentioning
confidence: 99%
“…Previous experience [5,11] had shown that diphosphonate administration and vitamin D status have profound influence on the exchange-diffusion of phosphate and calcium, respectively. These experimental manipulations were therefore tested for their effect, or lack of effect, on simple diffusion processes.…”
Section: Resultsmentioning
confidence: 99%
“…After 4 weeks on the diet vitamin D deficiency was confirmed by decreased growth rate, low levels of serum calcium and of 25-hydroxyvitamin D3. Further data on these experimental animals have been published elsewhere [5]. One group received 10/~1 of ethanol/day for 7 days (vitamin D deficient); other groups received ethanol containing 1,25(OH)2D3 at 2.6 pmoles/day (low dose), 26 pmoles/day (medium dose), or 260 pmoles/day (high dose).…”
Section: Methodsmentioning
confidence: 99%